Factors Affecting the Severity of Non-Hemorrhagic Stroke - Nurul Sri Wahyuni; Eky Okviana Armyati; Aisyah Miftakhur Rohmah (Masters Program in Public Health, 2026)
Background: Stroke severity is influenced by multiple factors, including sociodemographic characteristics, health access, and time of treatment. Timely recognition of stroke onset and early hospital arrival are critical to reduce neurological damage. However, evidence on these factors in local Indonesian settings remains limited. This study aimed to analyze factors affecting the severity of non-hemorrhagic stroke among patients at Darmayu Ponorogo Public Hospital. Subjects and Method: This cross-sectional study was conducted at Darmayu Ponorogo Public Hospital from July to September 2025. A total of 200 patients aged ≥18 years, diagnosed with non-hemorrhagic stroke, were selected using an accidental sampling method. The dependent variable was stroke severity, measured using the National Institutes of Health Stroke Scale (NIHSS). Independent variables included age, gender, education, occupation, income, health insurance, distance from home to hospital, and prehospital delay. Data were collected using structured questionnaires and medical records. Analysis was performed using simple logistic regression for bivariate analysis and multiple logistic regression for multivariate analysis. Results: Bivariate analysis showed that prehospital delay was most powerfully significant factor, where patients arriving within ≤4.5 hours had lower odds of severe stroke compared to those with delays >4.5 hours (OR = 0.20; p = 0.020). Multivariate analysis confirmed prehospital delay as an independent predictor (OR = 0.09; 95% CI = 0.01 to 0.62; p = 0.015). Conclusion: Prehospital delay is the most significant determinant of non-hemorrhagic stroke severity. Early hospital arrival (≤4.5 hours) substantially reduces the risk of severe stroke.